Manufacturing Sector Competitive Advantage: Case Study of South Sumatra Province using the Dynamic Shift Share Method - Sony Tian Dhora; Nairobi; Arivina Ratih Taher; Toto Gunarto; I Wayan Suparta (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
The manufacturing industry sector is one of the sectors that has become a priority and has become a reference for other sectors in the Province of South Sumatra. The manufacturing industry sector consists of 16 sub-sectors. This study aims to analyze the competitive advantage of the manufacturing sub-sector in South Sumatra Province in 2017-2021. The method used in this study uses dynamic shift share analysis. The results of this study obtained ten processing industry sub-sectors that have competitive advantages, namely coal and oil refining; food and Drink; textiles and apparel; leather goods from leather and footwear; paper and articles of paper for printing and reproduction of recorded media; chemical, pharmaceutical and traditional medicine; rubber, goods made of rubber and plastics; non-metal mineral goods; base metal; as well as furniture, and the remaining six sub-sectors do not have a competitive advantage. This competitive advantage assessment can be seen from the results of dynamic shift share analysis calculations which have positive and negative values. This means that if the value of competitive advantage is positive, it can be said that the sub-sector has a competitive advantage, while those that have a negative value then the sub-sector does not have a competitive advantage so that a development strategy is needed.